Efficacy and Safety of Lycoprozen®, a Novel Tomato-Based Food Supplement in Patients with Benign Prostatic Hyperplasia - Alberto, Cellini; Pier, Giorgio Natali; Manuela, Iezzi; Mauro, Piantelli; Vincenzo, Fogliano; Stefano, Iacobelli (International Journal of Nutrition, 2018)
Objective: To evaluate the efficacy and safety of a novel tomato-based food supplement on the lower urinary tract symptoms (LUTS) of patients with benign prostatic hyperplasia (BPH). Methods: Twenty patients with BPH were enrolled in this observational study. They were assigned to consume daily a sachet of Lycoprozen® (5 grams) dissolved in water for two months. Results: All patients successfully completed the Lycoprozen scheduled regimen and the IPSS (International Prostatic Symptom Score) questionnaire before and after treatment. No side effects due to treatment were noticed. In this preliminary study, we have found that Lycoprozen® significantly reduced the LUTS severity (paired t-test, two-tailed p value < 0.0001). The IPSS mean values before and after the treatment were 16.95+6.0 SD (range 31-6) and 12.2+4.9 SD (range 20-2), respectively. Conclusions: Based on these data, Lycoprozen® may represent a suitable alternative option for the treatment of symptomatic BPH patients which worth of further testing in a phase 2 prospective randomized double blind placebo controlled study. The treatment was without side effects and acceptance among patients was high.
Keywords: Benign Prostatic Hyperplasia